Pedagoški optimizem med utopijo in upanjem - Snoj, Alojzij Slavko (Bogoslovni vestnik, 2004)
Homo mechanicus is so strongly oriented towards usability, efficiency and productivity that this makes him increasingly insensitive to any higher quality of life. Is not his direct descendant homo electronicus even more strongly bewitched by the unlimited possibilities to appropriate nature, things and people? The importance of education or of a lack thereof is becoming rather obvious. The first part of the treatise deals with the anti-educational aberration brought by the anti-pedagogical wave. Then it shows some consequences of permissive education leading into a blind alley. The narcissistic and permissive model of education and socialization does not have any real future but leads into a utopia. Therefore some parents, teachers and educators look for alternative pedagogical models directing young people towards a successful life. In the second part of the treatise the author briefly mentions some positive attempts as a hope for the future: they are heralds of an alternative educational awareness and comprise educational models open to ethical and religious contents and values. Thus, the anthropological paradigm or the humanistic model is a more suitable alternative, which makes a young person not only knowledgeable and efficient, but also a keen supporter of ethical behaviour and tolerant co-existence as homo philantropicus. The visions of the young people, parents, educators and teachers confirm that preventive education with a broad positive educational supply is the only way to change the insipid pedagogical optimism into an attainable hope.
Keywords: anthropological paradigm; antropološka paradigma; education; humanistic model; humanistični model; pedagogika; pedagogy; religious instruction; Verski pouk; Vzgoja